Growth of elaborate microbial pinnacles in Lake Vanda, Antarctica. Issue 6 (29th July 2016) - Sumner, D. Y.; Jungblut, A. D.; Hawes, I.; Andersen, D. T.; Mackey, T. J.; Wall, K.
Abstract: Microbial pinnacles in ice‐covered Lake Vanda, McMurdo Dry Valleys, Antarctica, extend from the base of the ice to more than 50 m water depth. The distribution of microbial communities, their photosynthetic potential, and pinnacle morphology affects the local accumulation of biomass, which in turn shapes pinnacle morphology. This feedback, plus environmental stability, promotes the growth of elaborate microbial structures. In Lake Vanda, all mats sampled from greater than 10 m water depth contained pinnacles with a gradation in size from <1‐mm‐tall tufts to pinnacles that were centimeters tall. Small pinnacles were cuspate, whereas larger ones had variable morphology. The largest pinnacles were up to ~30 cm tall and had cylindrical bases and cuspate tops. Pinnacle biomass was dominated by cyanobacteria from the morphological and genomic groups Leptolyngbya, Phormidium, and Tychonema . The photosynthetic potential of these cyanobacterial communities was high to depths of several millimeters into the mat based on PAM fluorometry, and sufficient light for photosynthesis penetrated ~5 mm into pinnacles. The distribution of photosynthetic potential and its correlation to pinnacle morphology suggests a working model for pinnacle growth. First, small tufts initiate from random irregularities in prostrate mat. Some tufts grow into pinnacles over the course of ~3 years. As pinnacles increase in size and age, their interiors become colonized by a more diverse community of cyanobacteria with high photosynthetic potential. Biomass accumulation within this subsurface community causes pinnacles to swell, expanding laminae thickness and creating distinctive cylindrical bases and cuspate tops. This change in shape suggests that pinnacle morphology emerges from a specific distribution of biomass accumulation that depends on multiple microbial communities fixing carbon in different parts of pinnacles. Similarly, complex patterns of biomass accumulation may be reflected in the morphology of elaborate ancient stromatolites.